Insufficient Sleep and Alzheimer’s Disease: Potential Approach for Therapeutic Treatment Methods - Dieu Quynh Trinh; Nhu Huynh Mai; Toan Duc Pham (Brain Sciences)
The interaction between Alzheimer’s disease (AD) and sleep deprivation has recently gained attention in the scientific literature, and recent advances suggest that AD epidemiology management should coincide with the management of sleeping disorders. This review focuses on the aspects of the mechanisms underlying the link between AD and insufficient sleep with progressing age. We also provide information which could serve as evidence for future treatments of AD from the early stages in connection with sleep disorder medication.